Optical Properties and Electrochemical Performance of LiFePO4 Thin Films Deposited on Transparent Current Collectors - Lee, HyunSeok; Yim, Haena; Kim, Kwang-Bum; Choi, Ji-Won (AMER SCIENTIFIC PUBLISHERS, 2015)
LiFePO4 thin film cathodes are deposited on various transparent conducting oxide thin films on glass, which are used as cathode current collectors. The XRD patterns show that the thin films have the phase of LiFePO, with an ordered olivine structure indexed to the orthorhombic Pmna space group. LiFePO4 thin film deposited on various TOO glass substrates exhibits transmittance of about 53%. The initial specific discharge capacities of LiFePO4 thin films are 25.0 mu Ah/cm(2) . mu m on FTO, 33.0 mu Ah/cm(2). mu m on ITO, and 13.0 mu Ah/cm(2) . mu m on AZO coated glass substrates. Interestingly, the retention capacities of LiFePO4 thin films are 76.0% on FTO, 31.2% on ITO, and 37.7% on AZO coated glass substrates at 20th cycle. The initial specific discharge capacity of the LiFePO4/FTO electrode is slightly lower, but the discharge capacities of the LiFePO4/FTO electrode relatively decrease less than those of the others such as LiFePO4/ITO and LiFePO4/AZO with cycling. The results reported here provide the high transparency of LiFePO4 thin films cathode materials and the good candidate as FTO current collector of the LiFePO4 thin film cathode of transparent thin film rechargeable batteries due to its high transparency and cyclic retention.
Keywords: POSITIVE-ELECTRODE MATERIALS; LITHIUM; COMPOSITE; CELLS